Effects of feeding graded levels of Ractopamine (paylean TM) on pig performance in a commercial finishing facility - R G Main; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2001)
A total of 880 pigs were used in a 21-day trial conducted in a commercial research facility to determine the influence of feeding graded levels (0, 4.5, 6.75, and 9.0 g/ton) of ractopamine HCl (PayleanTM, Elanco Animal Health) on pig performance and carcass composition. Ractopamine supplementation improved ADG 17 to 22% and F/G 12 to 20%. Increasing ractopamine dosages resulted in improved F/G, but similar ADG. With the exception of a tendency to increase yield, carcass parameters were not different among treatments. Ractopamine supplementation resulted in improved economic returns ($2.55 to $3.20/pig), which were due to the improvements in carcass weights (80%) and lean premium (20%).; Swine Day, Manhattan, KS, November 15, 2001
Keywords: Swine day; 2001; Kansas Agricultural Experiment Station contribution; no. 02-132-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 880; Swine; Ractopamine; Paylean; Economics